Association Between Iron-Related Protein Lipocalin 2 and Cognitive Impairment in Cerebrospinal Fluid and Serum - das Neves, Sofia Pereira; Taipa, Ricardo; Marques, Fernanda; Soares Costa, Patrício; Monárrez-Espino, Joel; Palha, Joana A.; Kivipelto, Miia (Frontiers in Aging Neuroscience, 2021)
Worldwide increase in longevity is bringing novel challenges to public health and health care professionals. Cognitive impairment in the elderly may compromise living conditions and precede Alzheimer’s disease (AD), the most prevalent form of dementia. Therefore, finding molecular markers associated with cognitive impairment is of crucial importance. Lipocalin 2 (LCN2), an iron-related protein, has been suggested as a potential marker for mild cognitive impairment (MCI) and AD. This study aimed at investigating the association between LCN2 measured in serum and cerebrospinal fluid (CSF) with cognitive impairment. A cross-sectional design based on two aging cohorts was used: individuals diagnosed with subjective cognitive complains (SCC), MCI and AD from a Swedish memory clinic based cohort, and individuals diagnosed with SCC and AD from a Portuguese cohort. Binary logistic [for the outcome cognitive impairment (MCI+AD) in the Swedish cohort and AD in the Portuguese cohort] and multinomial logistic [for the outcomes MCI and AD] regression analyses were used. No associations were found in both cohorts when controlling for sex, education and age. This explanatory study suggests that the association between serum and CSF LCN2 concentrations with cognitive impairment reported in the literature must be further analyzed for confounders.